Simple Spectrophotometric Methods for the Estimation of Ofloxacin in Dosage Forms - Basu, S.K.; Krishnamoorthy, B. (Asian Journal of Chemistry, 2010)
For the estimation of ofloxacin from dosage forms two simple, sensitive, visible and UV spectrophotometric methods were developed. The visible method is based on the formation of an amber coloured complex with ferric chloride. The coloured product is quantitated spectrophotometrically at 381 nm and was found to obey the Beer's law in the concentration range of 12-50 μg mL-1. The UV method is based on the ionization of ofloxacin in acid medium and the maximum absorption was found at 291 nm and obeyed the Beer's law in the concentration range of 2-10 μg mL-1. Both the proposed methods were applied for estimation of different ofloxacin tablets and infusion with mean percentage accuracies of 103.2 ± 4.1, 104.4 ± 2.2, 99.6 ± 3.08 and 99.9, respectively with visible spectrophotometric method and 101.0 ± 0.916, 99.03 ± 1.65 and 99.36 ± 1.04, respectively with UV spectrometric method.